Frontiers in therapeutic development of allopregnanolone for Alzheimer’s disease and other neurological disorders - Irwin, Ronald W.; Solinsky, Christine M.; Brinton, Roberta Diaz (Frontiers in Cellular Neuroscience, 2014)
Allopregnanolone (Allo), a neurosteroid, has emerged as a promising promoter of endogenous regeneration in brain. In a mouse model of Alzheimer’s disease, Allo induced neurogenesis, oligodendrogenesis, white matter generation and cholesterol homeostasis while simultaneously reducing β-amyloid and neuroinflammatory burden. Allo activates signaling pathways and gene expression required for regeneration of neural stem cells and their differentiation into neurons. In parallel, Allo activates systems to sustain cholesterol homeostasis and reduce β-amyloid generation. To advance Allo into studies for chronic human neurological conditions, we examined translational and clinical parameters: dose, regimen, route, formulation, outcome measures, and safety regulations. A treatment regimen of once per week at sub-sedative doses of Allo was optimal for regeneration and reduction in Alzheimer’s pathology. This regimen had a high safety profile following chronic exposure in aged normal and Alzheimer’s mice. Formulation of Allo for multiple routes of administration has been developed for both preclinical and clinical testing. Preclinical evidence for therapeutic efficacy of Allo spans multiple neurological diseases including Alzheimer’s, Parkinson’s, multiple sclerosis, Niemann-Pick, diabetic neuropathy, status epilepticus, and traumatic brain injury. To successfully translate Allo as a therapeutic for multiple neurological disorders, it will be necessary to tailor dose and regimen to the targeted therapeutic mechanisms and disease etiology. Treatment paradigms conducted in accelerated disease models in young animals have a low probability of successful translation to chronic diseases in adult and aged humans. Gender, genetic risks, stage and burden of disease are critical determinants of efficacy. This review focuses on recent advances in development of Allo for Alzheimer’s disease that have the potential to accelerate therapeutic translation for multiple unmet neurological needs.